Acrophobia impairs visual exploration and balance during standing and walking. (26th February 2015) - Brandt, Thomas; Kugler, Günter; Schniepp, Roman; Wuehr, Max; Huppert, Doreen
Abstract : This review shows that persons with visual height intolerance or acrophobia exhibit typical restrictions of visual exploration and imbalance during stance and locomotion when exposed to heights. Eye and head movements are reduced, and gaze freezes to the horizon. Eye movements tend to be horizontal saccades during stance and vertical saccades during locomotion. Body posture is characterized by a stiffening of the musculoskeletal system with increased open‐loop diffusion activity of body sway, a lowered sensory feedback threshold for closed‐loop balance control, and increased co‐contraction of antigravity leg and neck muscles. Walking is slow and cautious, broad‐based, consisting of small, flat‐footed steps with less dynamic vertical oscillation of the body and head. Anxiety appears to be the critical symptom that causes the typical but not specific eye and body motor behavior, which can be described as tonic immobility. Guidelines for preventing acrophobia, which could be an add‐on to behavioral therapy, are provided.